2022
DOI: 10.1002/jcp.30923
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte TLR2 and TLR7 contribute to chronic itch through pruritic cytokines and chemokines in mice

Abstract: Although neuronal Toll-like receptors (TLRs) (e.g., TLR2, TLR3, and TLR7) have been implicated in itch sensation, the roles of keratinocyte TLRs in chronic itch are elusive.Herein, we evaluated the roles of keratinocyte TLR2 and TLR7 in chronic itch under dry skin and psoriasis conditions, which was induced by either acetone-ether-water treatment or 5% imiquimod cream in mice, respectively. We found that TLR2 and TLR7 signaling were significantly upregulated in dry skin and psoriatic skin in mice. Chronic itch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
(112 reference statements)
2
1
0
Order By: Relevance
“…It was also shown that the level of IL-6 in the serum of pSS patients was much higher, which was proven to be positively connected with TLR7 expression. Keratinocytes stimulated the production of in ammatory molecules, including IL-6, in the psoriasis mouse model via TLR2 and TLR7 signaling pathways, leading to illness [25]. This corresponds to our discovery trend.…”
Section: Discussionsupporting
confidence: 80%
“…It was also shown that the level of IL-6 in the serum of pSS patients was much higher, which was proven to be positively connected with TLR7 expression. Keratinocytes stimulated the production of in ammatory molecules, including IL-6, in the psoriasis mouse model via TLR2 and TLR7 signaling pathways, leading to illness [25]. This corresponds to our discovery trend.…”
Section: Discussionsupporting
confidence: 80%
“…12 These results suggest that sevoflurane exposure promotes neuroinflammation. KEGG pathway analysis uncovered notable enrichment in starch and sucrose metabolism, carbohydrate digestion and absorption, IL-17 signaling pathway, TNF-α signaling pathway, and chemokine signaling pathway following sevoflurane treatment (Figure 1D), which is consistent with previous reports showing the secretion of inflammatory and oxidative stress mediators are associated with neurological diseases such as multiple sclerosis (MS), 15 chronic itch 16 and experimental autoimmune encephalomyelitis (EAE). 17,18 Microglial activation-mediated neuroinflammation plays an important role in neurodegenerative disease progression.…”
Section: Sevoflurane Induced Inflammatory Gene Programs In Hippocampussupporting
confidence: 90%
“…For example, TLR7 mRNA and protein were clearly detected in primary human keratinocytes, which were further increased by induction of differentiation by calcium, 30 and both cultured human keratinocyte cells and mouse skin were reported to express TLR7 and respond to a TLR7 agonist. 31 Moreover, TLR7 protein expression was detected in normal human skin by immunostaining, which was further increased by IL-17. 32 Our current findings are consistent with these recent reports further supporting the role of TLR7 in human and mouse keratinocytes.…”
Section: Discussionmentioning
confidence: 97%
“…However, several more recent studies demonstrated TLR7 expression in keratinocytes. For example, TLR7 mRNA and protein were clearly detected in primary human keratinocytes, which were further increased by induction of differentiation by calcium, 30 and both cultured human keratinocyte cells and mouse skin were reported to express TLR7 and respond to a TLR7 agonist 31 . Moreover, TLR7 protein expression was detected in normal human skin by immunostaining, which was further increased by IL‐17 32 .…”
Section: Discussionmentioning
confidence: 97%